A Multicenter, Randomized, Controlled Study to Investigate Extending the Time for Thrombolysis in Emergency Neurological Deficits with Intra-Arterial Therapy (EXTEND-IA). Issue 1 (January 2014) - Campbell, Bruce C. V.; Mitchell, Peter J.; Yan, Bernard; Parsons, Mark W.; Christensen, Søren; Churilov, Leonid; Dowling, Richard J.; Dewey, Helen; Brooks, Mark; Miteff, Ferdinand; Levi, Christopher; Krause, Martin; et al.
Background and Hypothesis: Thrombolysis with tissue plasminogen activator is proven to reduce disability when given within 4.5 h of ischemic stroke onset. However, tissue plasminogen activator only succeeds in recanalizing large vessel arterial occlusion in a minority of patients. We hypothesized that anterior circulation ischemic stroke patients, selected with 'dual target' vessel occlusion and evidence of salvageable brain using computed tomography or magnetic resonance imaging 'mismatch' within 4.5 h of onset, would have improved reperfusion and early neurological improvement when treated with intra-arterial clot retrieval after intravenous tissue plasminogen activator compared with intravenous tissue plasminogen activator alone. Study Design: EXTEND-IA is an investigator-initiated, phase II, multicenter prospective, randomized, open-label, blinded-endpoint study. Ischemic stroke patients receiving standard 0.9 mg/kg intravenous tissue plasminogen activator within 4.5 h of stroke onset who have good prestroke functional status (modified Rankin Scale <2, no upper age limit) will undergo multimodal computed tomography or magnetic resonance imaging. Patients who also meet dual target imaging criteria: vessel occlusion (internal carotid or middle cerebral artery) and mismatch (perfusion lesion: ischemic core mismatch ratio >1.2, absolute mismatch >10 ml, ischemic core volume <70 ml) will be randomized to either clot retrieval with the Solitaire FR device after full dose intravenous tissue plasminogen activator, or tissue plasminogen activator alone. Study Outcomes: The coprimary outcome measure will be reperfusion at 24 h and favorable clinical response (reduction in National Institutes of Health Stroke Scale by ≥8 points or reaching 0–1) at day 3. Secondary outcomes include modified Rankin Scale at day 90, death, and symptomatic intracranial hemorrhage.